2023
DOI: 10.3389/fmech.2023.1261017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wind turbine flow through nacelle-mounted lidars: a review

Stefano Letizia,
Peter Brugger,
Nicola Bodini
et al.

Abstract: This article provides a comprehensive review of the most recent advances in the planning, execution, and analysis of inflow and wake measurements from nacelle-mounted wind Doppler lidars. Lidars installed on top of wind turbines provide a holistic view of the inflow and wake characteristics required to characterize and optimize wind turbine performance, carry out model validation and calibration, and aid in real-time control. The need to balance the enhanced capabilities and limitations of lidars compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…The research mainly uses CFD to numerically simulate the aerodynamic sensors, gyroscopes, wind speed sensors, and pressure sensors, and analyze the aerodynamic characteristics of multi rotor unmanned aerial vehicles. Since the AC of the multi-rotor vehicle has high requirements on the distribution of pressure and velocity fields, the iterative method selected for the study is the SIMPLE algorithm, which is mainly used to solve the numerical simulation of incompressible flow (Letizia et al, 2023).…”
Section: Numerical Simulations Of Aerodynamic Characteristicsmentioning
confidence: 99%
“…The research mainly uses CFD to numerically simulate the aerodynamic sensors, gyroscopes, wind speed sensors, and pressure sensors, and analyze the aerodynamic characteristics of multi rotor unmanned aerial vehicles. Since the AC of the multi-rotor vehicle has high requirements on the distribution of pressure and velocity fields, the iterative method selected for the study is the SIMPLE algorithm, which is mainly used to solve the numerical simulation of incompressible flow (Letizia et al, 2023).…”
Section: Numerical Simulations Of Aerodynamic Characteristicsmentioning
confidence: 99%
“…They offer remote sensing and are able to provide a great characterization of the future incoming flow, enabling feedforward approaches (Letizia et al, 2023;Scholbrock et al, 2016). Though industrial use of LiDARs for control applications has been reported (Raach, 2021), their cost, complexity of installation, or need for synchronization with the SCADA system still limit their broad use.…”
mentioning
confidence: 99%